A Low-Voltage Broadband D-Band BPSK Modulator for a PMCW Radar Transmitter in 22 nm FDSOI - Engelmann, Andre; Probst, Florian; Hetterle, Philip; Weigel, Robert; Dietz, Marco (Asia-Pacific Microwave Conference 2022 (APMC), 2022)
This work presents a broadband low-voltage binary-phase-shift-keying (BPSK) modulator operating in the D-band. The modulator is intended for a phase-modulated continuous-wave (PMCW) radar transmitter with a chip rate of up to 12.5 Gb/s and integrated into an advanced 22 nm fully-depleted silicon-on-insulator (FDSOI) technology. The circuit covers a bandwidth of 34 GHz at a carrier frequency of 140 GHz with a maximum conversion gain of 2.5 dB. A 1 dB output compression point of −7.2 dBm is reached while consuming 27 mW DC-Power at a supply voltage of only 0.8 V and a circuit core area of 0.051 sqm
Keywords: Binary-phase-shift-keying (BPSK) modulator; CMOS; D-band; FDSOI; MMIC; phase-modulated continuous-wave (PMCW) radar.